Teaching Tenses Effectively - Hafiz, M. Fahrezy Al; Harahap, Rizqil Aulia Balqis; Nadiyyana, Siti; Putri, Varisha Naila; Lubis, Yani (The Future of Education Journal, 2025)
Mastering tenses in English is a common challenge for Indonesian students due to differences in structure and time concepts between English and their native language. This article explores effective strategies for teaching tenses by emphasizing communicative approaches, the use of visual media, group discussions, peer correction, and the integration of metacognitive strategies. This study uses a descriptive qualitative approach through literature review. The results indicate that teaching tenses through reflective, participatory, and collaborative activities significantly improves students’ understanding of time structure in English. With the support of teachers as active facilitators, students become more independent and confident in using tenses accurately in real communication contexts.